Super-hydrophobic modified tencel fabric and preparation method thereof

By modifying the Tennis fabric with environmentally friendly materials such as chitosan, ZIF-8 and tung oil, the defects of existing fabrics in terms of soap-resistant fastness are solved, and the superhydrophobic performance is improved, and the material is environmentally friendly and harmless.

CN119777155AActive Publication Date: 2025-04-08NANTONG LOVER APPL +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411867421.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-18
Publication Date
2025-04-08
Estimated Expiration
2044-12-18

AI Technical Summary

Technical Problem

The existing superhydrophobic modified fabrics have defects in fastness, especially in terms of soap-resistant fastness, and the modification reagents used are harmful to the environment.

Method used

The Tensil fabric is modified by environmentally friendly materials such as chitosan, zeolite imidazole skeleton (ZIF-8) and tung oil. The hydrophobic properties of the fabric are improved by heat treatment, soaking and in-situ growth of ZIF-8, and the effect between the soap washing liquid and the hydrophobic coating is used to improve the soap washing fastness.

Benefits of technology

The prepared superhydrophobic modified tin wire fabric has an initial surface contact angle of greater than or equal to 145°, and the hydrophobic performance increases with the increase of the number of soap washings. The material is fluorine-free, non-toxic and harmless, and is green and environmentally friendly.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119777155A_ABST
    Figure CN119777155A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a super-hydrophobic modified tencel fabric, which comprises the following steps: immersing a pretreated tencel fabric in an acetic acid solution of chitosan, and then controlling the liquid carrying rate of a cloth cover to be 70-90%; carrying out heat treatment on the tencel fabric with the chitosan solution; immersing the tencel fabric subjected to heat treatment in an aqueous solution of zinc acetate dihydrate for 0.1-0.5 h, then adding an aqueous solution of dimethylimidazole, stirring and standing for reaction, taking out the tencel fabric after the reaction is finished, washing with water and drying; immersing the dried tencel fabric in an ethanol solution of tung oil, standing, and then controlling the liquid carrying rate of the fabric surface to be 40-70%; and taking out the tencel fabric, washing with water, drying, and placing in air for 10-30 days to obtain the super-hydrophobic modified tencel fabric. Compared with an unmodified tencel fabric, the super-hydrophobic modified tencel fabric obtained by the preparation method based on the chitosan, the zeolite imidazate framework material and the tung oil has a super-hydrophobic effect, and the hydrophobic property of the super-hydrophobic modified tencel fabric is improved along with the increase of soaping times.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of fabric modification and processing, and in particular to a preparation method for super-hydrophobic modification of Tencel fabric by using tung oil, chitosan and zeolite imidazolate skeleton (ZIF-8), and super-hydrophobic modified Tencel fabric prepared by the preparation method, wherein the initial surface contact angle of the Tencel fabric is greater than or equal to 145°. Background Art

[0002] Tencel fabric is an excellent material that is comfortable, breathable, renewable and biodegradable, providing an environmentally friendly and sustainable plant-based alternative to synthetic materials. With the progress of the times, consumers are increasingly favoring functional fabric materials. Among them, super-hydrophobic Tencel fabric has broad application prospects in high-end ties, scarves, tablecloths, household items and other fields due to its unique properties such as anti-fouling and self-cleaning. It can also solve the problem of poor waterproofness of sand-washed lyocell fabrics in woven clothing fabrics.

[0003] Tencel belongs to regenerated cellulose fiber, and its superhydrophobic modification method mainly draws on the modification method of cotton fabric. The materials used in the existing methods of superhydrophobic modification of cotton fabric have certain harm to the environment. For example, the long-chain fluorine-containing reagents are used to hydrophobically modify the fabric. Long-chain fluorine-containing reagents have extremely strong stability and are difficult to degrade. They will cause irreparable damage to the environment and human body and have been gradually banned. Zeolite imidazolate framework material (ZIF-8) is a popular material that has emerged in recent years and is widely used in catalysis, adsorption, and sensing. However, there is currently little research on the application of ZIF-8 in the functional modification of textiles.

[0004] In addition, the super-hydrophobic modified fabrics reported so far still have large defects in fastness (such as soap washing fastness). Therefore, it is a direction worth studying to find more environmentally friendly materials to prepare durable super-hydrophobic Tencel fabrics. In previous reports, researchers often start with improving the fastness between the modifying agent and the substrate for the improvement of the durability of super-hydrophobic fabrics, such as establishing a covalent bond of fastness between the modifying agent and the substrate. The fabrics treated in this way have been significantly improved in fastness to soap washing. However, research on improving fastness to soap washing by using the action between soaping liquid and fabric hydrophobic coating has not yet been reported.

[0005] The disclosure of the above background technology content is only used to assist in understanding the inventive concept and technical solution of the present invention. It does not necessarily belong to the prior art of this patent application. In the absence of clear evidence that the above content has been disclosed before the filing date of this patent application, the above background technology should not be used to evaluate the novelty and creativity of the present application. Summary of the invention

[0006] In view of this, in order to overcome the defects of the prior art, the purpose of the present invention is to provide a method for preparing a super-hydrophobic modified Tencel fabric, so as to prepare a super-hydrophobic modified Tencel fabric, whose initial surface contact angle is greater than or equal to 145°, and whose hydrophobic performance can be improved with the increase of the number of soap washings.

[0007] In order to achieve the above object, the present invention adopts the following technical solutions:

[0008] A method for preparing a super-hydrophobic modified Tencel fabric comprises the following steps:

[0009] The pretreated Tencel fabric is immersed in the acetic acid solution of chitosan, and then the liquid carrying rate of the fabric surface is controlled to be 70%-90%;

[0010] The Tencel fabric with the chitosan solution is subjected to heat treatment at a temperature of 140-160° C. for 1-5 minutes;

[0011] The heat-treated Tencel fabric is immersed in an aqueous solution of zinc acetate dihydrate for 0.1-0.5 hours, and then an aqueous solution of dimethylimidazole is added, stirred and allowed to stand for reaction, and after the reaction is completed, the Tencel fabric is taken out, washed and dried; ZIF-8 is grown in situ; the introduction of ZIF-8 on the surface of the textile can significantly increase the surface roughness and give the textile hydrophobic properties;

[0012] The dried Tencel fabric is immersed in the ethanol solution of tung oil and allowed to stand, and then the liquid carrying rate of the fabric surface is controlled to be 40%-70%;

[0013] The Tencel fabric is taken out, washed and dried, and placed in air for 10-30 days to obtain the super-hydrophobic modified Tencel fabric. The super-hydrophobic modified Tencel fabric can improve the soap washing fastness by utilizing the interaction between the soap washing liquid and the hydrophobic coating of the Tencel fabric.

[0014] According to some preferred implementation aspects of the present invention, the acetic acid solution of chitosan is formed by dissolving chitosan in an acetic acid solution with a concentration of 1%-3%, and the concentration of chitosan in the acetic acid solution of chitosan is 2%-4%.

[0015] According to some preferred embodiments of the present invention, the heat treatment is to use a heat press or a flat press to heat treat the Tencel fabric with the chitosan solution.

[0016] According to some preferred implementation aspects of the present invention, the concentration of the aqueous solution of zinc acetate dihydrate is 1%-2%; the concentration of the aqueous solution of dimethylimidazole is 15%-20%.

[0017] According to some preferred embodiments of the present invention, the stirring followed by standing the reaction is stirring for 0.1-1 hour and then standing for 12-36 hours.

[0018] According to some preferred implementation aspects of the present invention, the concentration of tung oil in the tung oil ethanol solution is 1%-3%; and the standing time is 2-10 minutes.

[0019] According to some preferred embodiments of the present invention, the pretreatment is: adding the Tencel fabric to a solution consisting of soap flakes, sodium carbonate and deionized water, gradually heating the solution to 65-75°C under stirring, and keeping the temperature; after the end, taking out the Tencel fabric, repeatedly washing it with deionized water and then drying it, and balancing and standing it at room temperature for 10-16 hours to obtain a clean Tencel fabric.

[0020] According to some preferred embodiments of the present invention, the surface contact angle of the prepared super-hydrophobic modified Tencel fabric is 145°-150°.

[0021] In some embodiments of the present invention, the method for preparing super-hydrophobic modified Tencel fabric specifically comprises the following steps:

[0022] (1) Pretreatment: Add the Tencel fabric to a solution consisting of soap flakes, sodium carbonate and deionized water, gradually heat it to 65-75°C while stirring, and keep it warm; after the end, take out the Tencel fabric, wash it repeatedly with deionized water and dry it, and let it stand at room temperature for 10-16 hours to obtain a clean Tencel fabric.

[0023] (2) Dissolve chitosan in an acetic acid solution with a concentration of 1-3% to form a chitosan acetic acid solution with a chitosan concentration of 2-4%. Then immerse the pretreated Tencel fabric in the solution and stir for 5-15 minutes.

[0024] (3) Take out the Tencel fabric and use a padder to control the liquid content of the fabric to be 70%-90%.

[0025] (4) Heat-treating the Tencel fabric with the chitosan solution in a hot press or a flat press for 1-5 minutes at a temperature of 140-160°C.

[0026] (5) Immerse the heat-treated Tencel fabric in a 1%-2% aqueous solution of zinc acetate dihydrate for 0.1-0.5 hours, then add a 15%-20% aqueous solution of dimethylimidazole, stir for 0.1-1 hour, and then stand for 12-36 hours. After the standing treatment, wash with water and dry.

[0027] (6) The dried Tencel fabric is immersed in an ethanol solution of tung oil with a concentration of 1% to 3%, taken out after 2 to 10 minutes, and the liquid carrying rate of the fabric surface is controlled to be 40% to 70% by using a padder.

[0028] (7) The Tencel fabric is taken out, washed and dried, and then placed in air for 10-30 days to obtain a super-hydrophobic modified Tencel fabric, the hydrophobic property of which increases with the increase of soap washing times.

[0029] The present invention also provides a method for improving the hydrophobic performance of the super-hydrophobic modified Tencel fabric, comprising the following steps: soaping the super-hydrophobic modified Tencel fabric for 1-30 times, preferably 5-20 times, and the surface contact angle of the modified Tencel fabric after soaping can be increased to 150°-170°. The soaping treatment method is carried out according to the standard "GB / T 3921-2008 Textiles. Color fastness test. Color fastness to soaping".

[0030] The present invention also provides a super-hydrophobic modified Tencel fabric prepared by the preparation method as described above, wherein the hydrophobic property of the super-hydrophobic modified Tencel fabric increases with the increase of soap washing times.

[0031] According to some preferred embodiments of the present invention, the surface contact angle of the super-hydrophobic modified Tencel fabric after soap washing is 150°-166°. Specifically, the surface contact angle of the super-hydrophobic modified Tencel fabric after 5 soap washings is 150°-153°; the surface contact angle after 10 soap washings is 153°-158°; the surface contact angle after 15 soap washings is 158°-164°; the surface contact angle after 20 soap washings is 164°-166°.

[0032] The principle of the present invention is: taking a Tencel fabric with a large number of hydroxyl groups in its molecular structure as a substrate, forming an ether bond with chitosan under the action of high-temperature heat treatment; then growing ZIF-8 in situ to provide a surface nanostructure required for hydrophobic performance; and finally further treating with tung oil to provide a low surface energy substance required for hydrophobic performance. The main component of tung oil is tung oil triglyceride, which will be hydrolyzed into unsaturated tung oil acid containing three conjugated double bonds under the action of alkali. Therefore, a large amount of tung oil acid will be produced on the surface of the modified hydrophobic Tencel fabric during the washing process of alkaline soap solution. There is an electrostatic attraction between the carboxyl group of tung oil acid and ZIF-8. At the same time, these tung oil acids can induce the ZIF-8 loaded on the surface of the Tencel fabric to produce a nano flower-like morphology, thereby significantly improving the surface roughness; on the other hand, the generation of tung oil acid further reduces the surface tension. Under the combined action of the two factors, the contact angle of the Tencel fabric during the soap washing process gradually increases to more than 150°, and super hydrophobic performance is obtained. And with the increasing number of soap washings, the contact angle of Tencel fabric can be increased to above 160°.

[0033] Due to the adoption of the above technical scheme, the present invention has the following advantages compared with the prior art: the preparation method of the super-hydrophobic modified Tencel fabric of the present invention is based on chitosan, zeolite imidazolate skeleton material and tung oil to obtain a Tencel fabric, which has a super-hydrophobic effect compared with the unmodified Tencel fabric; the hydrophobic performance of the prepared modified Tencel fabric can be gradually improved with the increase of the number of soap washings, the materials used are fluorine-free, non-toxic and harmless, green and environmentally friendly, and the preparation method is simple. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0035] Figure 1 The surface microstructures of Comparative Example 1 (a, only pre-treated Tencel fabric), Comparative Example 2 (b, chitosan and ZIF-8 modified Tencel fabric), and Example 1 (c, chitosan, ZIF-8 and tung oil modified Tencel fabric);

[0036] Figure 2 Surface contact angles (water) of Comparative Example 1 (only pretreated Tencel fabric), Comparative Example 2 (Chitosan and ZIF-8 modified Tencel fabric), and Example 1 (Chitosan, ZIF-8, and tung oil modified Tencel fabric);

[0037] Figure 3 The surface microstructures of the super-hydrophobic modified Tencel fabric prepared in Example 1 after being soaped for 5 times (a), 10 times (b), 15 times (c), and 20 times (d);

[0038] Figure 4 The surface contact angle (water) of the super-hydrophobic modified Tencel fabric prepared in Example 1 after being soaped 5 times (a), 10 times (b), 15 times (c), and 20 times (d);

[0039] Figure 5 The surface microstructures of the super-hydrophobic modified Tencel fabrics prepared in Example 2 (a) and Example 3 (b) after five soap washings. DETAILED DESCRIPTION

[0040] In order to enable those skilled in the art to better understand the technical solution of the present invention, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.

[0041] The Tencel fabric with super-hydrophobic properties and the preparation method thereof of the present invention not only have super-hydrophobic properties, but also the hydrophobicity will increase with the increase of soap washing times, and the super-hydrophobicity will not decrease with the increase of soap washing times. Specifically, the preparation method of the super-hydrophobic modified Tencel fabric of the present invention specifically comprises the following steps:

[0042] (1) Pretreatment: Add the Tencel fabric to a solution consisting of soap flakes, sodium carbonate and deionized water, gradually heat it to 65-75°C while stirring, and keep it warm; after the end, take out the Tencel fabric, wash it repeatedly with deionized water and dry it, and let it stand at room temperature for 10-16 hours to obtain a clean Tencel fabric.

[0043] (2) Dissolve chitosan in an acetic acid solution with a concentration of 1-3% to form a chitosan acetic acid solution with a chitosan concentration of 2-4%. Then immerse the pretreated Tencel fabric in the solution and stir for 5-15 minutes.

[0044] (3) Take out the Tencel fabric and use a padder to control the liquid content of the fabric to be 70%-90%.

[0045] (4) Heat-treating the Tencel fabric with the chitosan solution in a hot press or a flat press for 1-5 minutes at a temperature of 140-160°C.

[0046] (5) Immerse the heat-treated Tencel fabric in a 1%-2% aqueous solution of zinc acetate dihydrate for 0.1-0.5 hours, then add a 15%-20% aqueous solution of dimethylimidazole, stir for 0.1-1 hour, and then stand for 12-36 hours. After the standing treatment, wash with water and dry. In situ growth of ZIF-8; Introducing ZIF-8 on the surface of textiles can significantly increase the surface roughness and give the textiles hydrophobic properties.

[0047] (6) The dried Tencel fabric is immersed in an ethanol solution of tung oil with a concentration of 1% to 3%. After 2 to 10 minutes, the fabric is taken out and a padder is used to control the liquid content of the fabric to be 40% to 70%.

[0048] (7) The Tencel fabric is taken out, washed and dried, and then placed in air for 10-30 days to obtain a super-hydrophobic modified Tencel fabric, the hydrophobic property of which increases with the increase of soap washing times.

[0049] Preprocessing:

[0050] Before using chitosan, ZIF-8 and tung oil to modify Tencel fabric, it is necessary to pretreat the Tencel fabric to remove dirt and impurities attached to the surface.

[0051] The pretreatment process in this embodiment is as follows: 2g of Tencel fabric is added to a solution consisting of 0.4g of soap flakes, 0.4g of sodium carbonate and 200mL of deionized water, and the temperature is gradually raised to 70°C under stirring, and the temperature is kept for 1 hour. After the heat preservation treatment, the Tencel fabric is taken out and repeatedly washed with deionized water for 5 times. Then, it is dried in a 75°C oven for 6 hours, and allowed to stand at room temperature for 12 hours to obtain a clean Tencel fabric.

[0052] Example 1

[0053] This embodiment provides a preparation method for obtaining super-hydrophobic modified Tencel fabric by functionally modifying Tencel fabric using chitosan, ZIF-8 and tung oil, which specifically comprises the following steps:

[0054] Glacial acetic acid was dissolved in 50 mL of deionized water to prepare an acetic acid solution with a concentration of 2%. Subsequently, 1.55 g of chitosan was dissolved in the obtained acetic acid solution to prepare a chitosan solution with a concentration of 3%.

[0055] 0.25 g of Tencel fabric was immersed in the obtained chitosan solution for 10 minutes with constant stirring, and then the Tencel fabric was taken out and the liquid carrying rate on the surface of the Tencel fabric was controlled to be 80% by a padder.

[0056] The Tencel fabric with chitosan solution was heat treated in a hot press for 3 minutes at a heat treatment temperature of 150°C.

[0057] Subsequently, the heat-treated Tencel fabric was immersed in a 1.44% aqueous solution of zinc acetate dihydrate, and a 17.22% aqueous solution of dimethylimidazole was added, stirred for 0.5 hours, and then allowed to stand for 24 hours. After the standing treatment, the Tencel fabric was repeatedly washed with water and dried.

[0058] The dried Tencel fabric was immersed in 50 mL of 2% tung oil ethanol solution, and was taken out after standing for 5 minutes. After washing and drying, the super-hydrophobic modified Tencel fabric was obtained.

[0059] Example 2

[0060] This embodiment provides a preparation method for obtaining super-hydrophobic modified Tencel fabric by functionally modifying Tencel fabric using chitosan, ZIF-8 and tung oil. The difference between this method and Embodiment 1 is only that the concentration of the ethanol solution of tung oil is different. The method specifically comprises the following steps:

[0061] Glacial acetic acid was dissolved in 50 mL of deionized water to prepare an acetic acid solution with a concentration of 2%. Subsequently, 1.55 g of chitosan was dissolved in the obtained acetic acid solution to prepare a chitosan solution with a concentration of 3%.

[0062] 0.25 g of Tencel fabric was immersed in the obtained chitosan solution for 10 minutes with constant stirring, and then the Tencel fabric was taken out and the liquid carrying rate on the surface of the Tencel fabric was controlled to be 80% by a padder.

[0063] The Tencel fabric with chitosan solution was heat treated in a hot press for 3 minutes at a heat treatment temperature of 150°C.

[0064] Subsequently, the heat-treated Tencel fabric was immersed in a 1.44% aqueous solution of zinc acetate dihydrate, and a 17.22% aqueous solution of dimethylimidazole was added, stirred for 0.5 hours, and then allowed to stand for 24 hours. After the standing treatment, the Tencel fabric was repeatedly washed with water and dried.

[0065] The dried Tencel fabric was immersed in 50 mL of 1% tung oil ethanol solution, and was taken out after standing for 5 minutes. After washing and drying, the super-hydrophobic Tencel fabric was obtained.

[0066] Example 3

[0067] This embodiment provides a preparation method for obtaining super-hydrophobic modified Tencel fabric by functionally modifying Tencel fabric using chitosan, ZIF-8 and tung oil. The difference between this method and Embodiment 1 is only that the concentration of the ethanol solution of tung oil is different. The method specifically comprises the following steps:

[0068] Glacial acetic acid was dissolved in 50 mL of deionized water to prepare an acetic acid solution with a concentration of 2%. Subsequently, 1.55 g of chitosan was dissolved in the obtained acetic acid solution to prepare a chitosan solution with a concentration of 3%.

[0069] 0.25 g of Tencel fabric was immersed in the obtained chitosan solution for 10 minutes with constant stirring, and then the Tencel fabric was taken out and the liquid carrying rate on the surface of the Tencel fabric was controlled to be 80% by a padder.

[0070] The Tencel fabric with chitosan solution was heat treated in a hot press for 3 minutes at a heat treatment temperature of 150°C. Subsequently, the heat-treated Tencel fabric was immersed in an aqueous solution of zinc acetate dihydrate with a concentration of 1.44%, and an aqueous solution of dimethylimidazole with a concentration of 17.22% was added, stirred for 0.5 hours, and then allowed to stand for 24 hours. After the standing treatment, the Tencel fabric was repeatedly washed with water and dried.

[0071] The dried Tencel fabric was immersed in 50 mL of 3% tung oil ethanol solution, left to stand for 5 minutes and then taken out. After washing and drying, the super-hydrophobic Tencel fabric was obtained.

[0072] Example 4

[0073] This embodiment provides a preparation method for obtaining super-hydrophobic modified Tencel fabric by functionally modifying Tencel fabric using chitosan, ZIF-8 and tung oil, which specifically comprises the following steps:

[0074] Glacial acetic acid was dissolved in 50 mL of deionized water to prepare an acetic acid solution with a concentration of 2%. Subsequently, 1.55 g of chitosan was dissolved in the obtained acetic acid solution to prepare a chitosan solution with a concentration of 3%.

[0075] 0.25 g of Tencel fabric was immersed in the obtained chitosan solution for 5 minutes with continuous stirring, and then the Tencel fabric was taken out and the liquid carrying rate on the surface of the Tencel fabric was controlled to be 80% by a padder.

[0076] The Tencel fabric with chitosan solution was heat treated in a hot press for 3 minutes at a heat treatment temperature of 160°C.

[0077] Subsequently, the heat-treated Tencel fabric was immersed in a 2% aqueous solution of zinc acetate dihydrate, and a 20% aqueous solution of dimethylimidazole was added, stirred for 0.5 hours, and then allowed to stand for 12 hours. After the standing treatment, the Tencel fabric was repeatedly washed with water and dried.

[0078] The dried Tencel fabric was immersed in 50 mL of 1% tung oil ethanol solution, left to stand for 2 minutes and then taken out. After washing and drying, the super-hydrophobic Tencel fabric was obtained.

[0079] Example 5

[0080] This embodiment provides a preparation method for obtaining super-hydrophobic modified Tencel fabric by functionally modifying Tencel fabric using chitosan, ZIF-8 and tung oil, which specifically comprises the following steps:

[0081] Glacial acetic acid was dissolved in 50 mL of deionized water to prepare an acetic acid solution with a concentration of 2%. Subsequently, 1.55 g of chitosan was dissolved in the obtained acetic acid solution to prepare a chitosan solution with a concentration of 3%.

[0082] 0.25 g of Tencel fabric was immersed in the obtained chitosan solution for 15 minutes with constant stirring, and then the Tencel fabric was taken out and the liquid carrying rate on the surface of the Tencel fabric was controlled to be 70% by a padder.

[0083] The Tencel fabric with chitosan solution was heat treated in a hot press for 5 minutes at a heat treatment temperature of 140°C. Subsequently, the heat-treated Tencel fabric was immersed in a 1% aqueous solution of zinc acetate dihydrate, and a 15% aqueous solution of dimethylimidazole was added, stirred for 0.5 hours, and then allowed to stand for 24 hours. After the standing treatment, the Tencel fabric was repeatedly washed with water and dried.

[0084] The dried Tencel fabric was immersed in 50 mL of 3% tung oil ethanol solution, left to stand for 5 minutes and then taken out. After washing and drying, the super-hydrophobic Tencel fabric was obtained.

[0085] Comparative Example 1

[0086] The Tencel fabric of this comparative example is the Tencel fabric that has only been subjected to the above-mentioned pretreatment.

[0087] Comparative Example 2

[0088] The difference between this comparative example and Example 1 is that only chitosan and ZIF-8 are used to modify the Tencel fabric, which specifically includes the following steps:

[0089] Glacial acetic acid was dissolved in 50 mL of deionized water to prepare an acetic acid solution with a concentration of 2%. Subsequently, 1.55 g of chitosan was dissolved in the obtained acetic acid solution to prepare a chitosan solution with a concentration of 3%.

[0090] 0.25 g of Tencel fabric was immersed in the obtained chitosan solution for 10 minutes with constant stirring, and then the Tencel fabric was taken out and the liquid carrying rate on the surface of the Tencel fabric was controlled to be 80% by a padder.

[0091] The Tencel fabric with chitosan solution was heat treated in a hot press for 3 minutes at a heat treatment temperature of 150°C.

[0092] Subsequently, the heat-treated Tencel fabric was immersed in a 1.44% aqueous solution of zinc acetate dihydrate, and a 17.22% aqueous solution of dimethylimidazole was added, stirred for 0.5 hours, and then allowed to stand for 24 hours. After the standing treatment, the Tencel fabric was repeatedly washed and dried to obtain a modified Tencel fabric.

[0093] Tests and Results

[0094] The modified Tencel fabric obtained in Example 1 was subjected to soap washing treatment, and then the morphology and surface contact angle were characterized, and compared with the modified Tencel fabrics obtained in Comparative Examples 1 and 2.

[0095] The soaping treatment method is carried out according to the standard "GB / T 3921-2008 Textiles. Color fastness test. Color fastness to soaping". The concentration of the soap solution is 5g / L, the bath ratio is 1:50, the rotation speed is (40±2)r / min, the temperature is 40°C, and every 30 minutes is recorded as one soaping. The modified Tencel fabric prepared according to the method of Example 1 was soaped 20 times, and the surface micromorphology and surface contact angle of the Tencel fabric after soaping 5, 10, 15, and 20 times were characterized respectively. The soaping process and characterization method of Example 2 and Example 3 are the same as those of Example 1.

[0096] Figure 1 The surface microstructures of Comparative Example 1 (a, only pre-treated Tencel fabric), Comparative Example 2 (b, chitosan and ZIF-8 modified Tencel fabric), and Example 1 (c, chitosan, ZIF-8 and tung oil modified Tencel fabric) are shown. Figure 1 It can be found that the surface of the pretreated Tencel fabric is relatively smooth. After modification with chitosan and ZIF-8, the surface of the Tencel fabric has an irregular scaly morphology, which is caused by the in-situ growth of ZIF-8 on the chitosan film on the surface of the Tencel fabric. Figure 1 As shown in Figure c), a film is formed on the outer surface of the Tencel fabric, which completely wraps the raised morphology.

[0097] Figure 2 Shown are the surface contact angles of Comparative Example 1 (only pre-treated Tencel fabric), Comparative Example 2 (Chitosan and ZIF-8 modified Tencel fabric), and Example 1 (Chitosan, ZIF-8 and tung oil modified Tencel fabric). It can be found from the figure that the contact angle of the Tencel fabric is 0°, which is caused by the presence of a large number of hydrophilic hydroxyl groups in the Tencel fabric structure. The contact angle of the Tencel fabric after modification with chitosan and ZIF-8 increased to 60.9°, because the introduction of chitosan and ZIF-8 increased the roughness of the Tencel fabric surface. After being treated with tung oil, the contact angle of the Tencel fabric reached 146.6°, showing hydrophobic properties. This is because tung oil, as a natural low surface energy substance, can reduce the surface tension of the Tencel fabric.

[0098] Figure 3 and Figure 4Shown are the changes in surface microstructure and contact angle of the modified Tencel fabric prepared according to the method of Example 1 after being soaped 5 times (a), 10 times (b), 15 times (c), and 20 times (d). During the soaping process, tung oil reacts with alkali to produce a large amount of tung oil acid. These tung oil acids can induce changes in the morphological structure of ZIF-8, resulting in a flaky morphology and accumulation between layers, and eventually forming nanoflowers of various shapes. In addition, as the number of soaping times gradually increases, it can be observed that the number of nanoflowers produced on the surface of the Tencel fabric also increases accordingly, and the size of the nanoflowers gradually decreases. The rougher the substrate surface, the more conducive it is to obtaining super-hydrophobic properties. These gradually shrinking nanoflowers play a vital role in improving the super-hydrophobic properties of the Tencel fabric as the number of soaping times increases. Figure 4 As shown, the surface contact angle of the modified Tencel fabric gradually increased from 151.9° to 164.8° with the increase of soap washing times.

[0099] Figure 5 The figure shows the surface microscopic morphology of the modified Tencel fabric prepared according to the method of Example 2 (a) and Example 3 (b) after being soaped five times. Figure 5 The results show that the Tencel fabric modified with tung oil at a lower (1%) or higher (3%) concentration will produce nanoflowers during the soaping process, and the surface contact angle after 5 soapings is greater than 150°, showing super hydrophobic properties. Figure 3 Compared with the Tencel fabric modified with 2% tung oil as shown in a, there are still some differences. When the Tencel fabric is modified with 1% tung oil, the nanoflowers produced after 5 soap washings are smaller in size. This is because there is less tung oil attached to the surface of the Tencel fabric, which is quickly hydrolyzed into tung oil acid in fewer soap washing cycles. Such a result means that after fewer soap washings, the morphology of these nanoflowers will face damage caused by soap washing. When the Tencel fabric is modified with 3% tung oil, the nanoflowers produced after 5 soap washings are small and few in size. This may be because the higher concentration of tung oil produces a very thick film on the surface of the Tencel fabric, isolating most of the tung oil acid from contact with ZIF-8. Combined with the above analysis and results, 2% concentration of tung oil (i.e., Example 1) is the optimal treatment solution.

[0100] The above results show that the chitosan, ZIF-8 and tung oil modified Tencel fabric prepared by the modification method of the present invention can impart hydrophobic properties to the Tencel fabric. It obtains super hydrophobic properties during the soaping process, and the hydrophobic properties gradually increase with the increase of soaping times.

[0101] The super-hydrophobic modified Tencel fabric of the present invention has hydrophobic performance that increases with the increase of soap washing times. The preparation method uses the Tencel fabric as a substrate and specifically comprises the following steps: (1) soaking in a chitosan solution; (2) heat treatment; (3) in-situ growth of a zeolite imidazolate framework (ZIF-8); and (4) soaking in an ethanol solution of tung oil. The Tencel fabric treated by the above steps has excellent hydrophobic performance, obtains super-hydrophobic performance during soap washing, and the super-hydrophobic performance gradually increases with the increase of soap washing times, and has broad application prospects.

[0102] The above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable people familiar with this technology to understand the contents of the present invention and implement them accordingly. They cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.

[0103] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

Claims

1. A method for preparing a super-hydrophobic modified Tencel fabric, characterized in that: The steps include: The pretreated Tencel fabric is immersed in the acetic acid solution of chitosan, and then the liquid carrying rate of the fabric surface is controlled to be 70%-90%; The Tencel fabric with the chitosan solution is subjected to heat treatment at a temperature of 140-160° C. for 1-5 minutes; The heat-treated Tencel fabric is immersed in an aqueous solution of zinc acetate dihydrate for 0.1-0.5 hours, and then an aqueous solution of dimethylimidazole is added, stirred and allowed to stand for reaction, and after the reaction is completed, the Tencel fabric is taken out, washed with water and dried; The dried Tencel fabric is immersed in the ethanol solution of tung oil and allowed to stand, and then the liquid carrying rate of the fabric surface is controlled to be 40%-70%; The Tencel fabric is taken out, washed and dried, and placed in the air for 10-30 days to obtain the super-hydrophobic modified Tencel fabric.

2. The preparation method according to claim 1, characterized in that: The chitosan acetic acid solution is formed by dissolving chitosan in an acetic acid solution with a concentration of 1%-3%. The concentration of chitosan in the chitosan acetic acid solution is 2%-4%.

3. The preparation method according to claim 1, characterized in that: The heat treatment is to use a hot press or a flat press to heat treat the Tencel fabric with the chitosan solution.

4. The preparation method according to claim 1, characterized in that: The concentration of the aqueous solution of zinc acetate dihydrate is 1%-2%; the concentration of the aqueous solution of dimethylimidazole is 15%-20%.

5. The preparation method according to claim 1, characterized in that: The reaction is allowed to stand for 12 to 36 hours after stirring for 0.1 to 1 hour.

6. The preparation method according to claim 1, characterized in that: The concentration of tung oil in the tung oil ethanol solution is 1%-3%; and the standing time is 2-10 minutes.

7. The preparation method according to claim 1, characterized in that: The pretreatment is as follows: adding the Tencel fabric to a solution consisting of soap flakes, sodium carbonate and deionized water, gradually heating up to 65-75° C. under stirring, and keeping the temperature; after the end, taking out the Tencel fabric, repeatedly washing it with deionized water and drying it, and balancing and standing it at room temperature for 10-16 hours to obtain a clean Tencel fabric.

8. The preparation method according to any one of claims 1 to 7, characterized in that: The surface contact angle of the prepared super-hydrophobic modified Tencel fabric is 145°-150°.

9. A super-hydrophobic modified Tencel fabric prepared by the preparation method according to any one of claims 1 to 8, characterized in that: The hydrophobicity of the super-hydrophobic modified Tencel fabric increases with the increase of soap washing times.

10. The super-hydrophobic modified Tencel fabric according to claim 9, characterized in that: The surface contact angle of the super-hydrophobic modified Tencel fabric after soap washing is 150°-166°.

Citation Information

Patent Citations

  • Method for jointly modifying polypropylene by ZnO / chitosan / ZIF-8, filter material and anti-virus mask

    CN112126154A

  • Preparation method of magnesium alloy super-hydrophobic coating based on zeolite imidazate framework

    CN112323116A

  • Super-hydrophobic paper as well as preparation method and application thereof

    CN114687235A

  • Super-hydrophilic-superoleophobic self-healing fabric and preparation method thereof

    CN114703665A

  • Graphite steel wire rode, graphite steel wire, and graphite steel for TV PEM nut part and methods for manufacturing the same

    KR1020230039008A